2021–2022 Florida Citrus Production Guide: Citrus Leafminer: CG098, rev. 3/2021 - Diepenbrock, Lauren Marie; Qureshi, Jawwad; Stelinski, Lukasz L. (EDIS, 2021)
Reviewed March 2021. There are no changes in recommendation from 2020.